The use of Horizon graphs to visualize bilateral biomechanical time-series of multiple joints - Okai-Nobrega, Liria Akie; Santos, Thiago Ribeiro Teles; Shimabukuro, Milton Hirokazu [UNESP]; Resende, Renan Alves; de Souza, Thales Rezende [UNESP]; da Fonseca, Sérgio Teixeira (Elsevier, 2021)
Movement analysis provides a vast amount of data, which, frequently, are not used in the clinical decision-making process. For example, traditional gait data visualization is based on a time-based display of joint angles, but part of the information is lost when these time-series are averaged across different gait strides. Horizon graph is a data display method that increases the density of time-series data by horizontally dividing and layering multiple filled line graphs. This higher data density increases the amount of information displayed in the same graph and, consequently, enables visual data comparisons between multiple time series. Horizon graph of kinematic data allows displaying several cycles of different joints and their respective continuous symmetry ratio between sides. The aim of this work is to introduce the Horizon graph as a method to analyze kinematic gait data and help to characterize its symmetry. Examples of Horizon graph application to running is offered. Horizon graph may prove to be a useful clinical tool to visualize kinematic time-series and facilitate their clinical interpretation. • Continuous gait time series is a powerful tool for clinical analysis. • Horizon graph, higher data density graph, increases the information displayed. • Horizon graph is a clinical tool to visualize kinematic curves.
Keywords: Clinical; Data visualization; Horizon Graph; Movement analysis; Running